Pelaksanaan Trias Usaha Kesehatan Sekolah (Uks)Di Sekolah Sma Pgri 1 Kota Mojokerto - Wicaksono, Arif; Basuki, Duwi (JURNAL KEPERAWATAN SEHAT, 2014)
UKS performing until now is felt still reducing corresponds to that expected, until 30% surrounding new currently SLTP and SMA at indonesian one performs to program UKS. There are many factor which constrain UKSS developing, amongst those teacher has had commitment and care to perform that program, medium the limited and prasarana, and UKSS energy that was coached. To the effect this research is subject to be identify Trias UKSs Performing at SMA PGRI 1 Mojokertos City. Observational design descriptive statistic with approaching cross sectional . Its population is exhaustive student as much 175 students and are taken 122 students as meenggunakans sample cluster random is sampling . This observational variable is Trias UKSs performing. Trias UKSs performing data is gathered by use of kuisioner Andrian Dargo S. is data further at o and analysed by descriptive statistic. menunjukans observational result plays favorites respondent to declare for Trias UKSs Performing at SMA PGRI 1 City Mojokerto is good as much 65 reponden (53,3%),adequately 28 (23%) and reducing 29 (23,8%). Its reducing is Trias UKSs performing caused by its reducing UKSS management, its reducing is facility, skills reducing is governing UKS and its reducing service program. UKSS ministering energy can perform program, counselling, and UKSS cadre training.Key word: performing, Trias UKS